Respuesta :

Answer:

We conclude that:

(f - g) (x) =   |7x| + 86  

Hence, option D is correct.

Step-by-step explanation:

Given

f(x) = 8|x| + 27

g(x) = 59 - |x|

To determine

(f - g)(x)

Using the formula

(f - g) (x) = f(x) - g(x)

substituting f(x) = 8|x| + 27 and g(x) = 59 - |x| in the formula

             = 8|x| + 27 + 59 - |x|

Group like terms

            = 8|x| - |x| + 27 + 59

            = |7x| + 27 + 59                ∵ 8|x| - |x| = 7x

            = |7x| + 86                         ∵ 27 + 59 = 86

Therefore, we conclude that:

(f - g) (x) =   |7x| + 86  

Hence, option D is correct.